MARKETING INNOVATIONS IN CROSS-BORDER PASSENGER TRANSPORTATION - Iryna Honcharova; Tetana Metil; Viktor Koval; Illia Neskhodovskyi (Agora International Journal of Economical Sciences (AIJES), 2023)
The development of innovations in various areas of economic activity has its own characteristics. There are a number of unique features for the development of passenger transport routes, which should be considered in more detail than in the planning of freight transport, and characterize this type of activity as particularly unique and requires a specialized approach in marketing innovations in this area. The presented article outlines the basic principles and concepts of the approach both when working with the material and technical base and when working with personnel in the course of planning and implementing innovations in passenger transportation. Particular attention is paid to the system of motivation for the implementation of the innovation process since the result of the introduction of innovation depends on the degree of motivation of potential subjects of the innovation process. Also, options for communication are considered both directly with potential consumers of the service created in the process of innovative activity and with local authorities in those regions where it is planned to carry out the innovative activity.
Keywords: 330